Impact of Corporate Governance in Supply Chain Management - Istianingsih Istianingsih (International Journal of Supply Chain Management, 2020)
Abstract— Collaborative governance plays a critical role in guiding the whole supply chain to achieve its strategic goals. This study aims to examine the impact of information provided via the disclosure of intellectual capital on the cost of equity capital. It also examines the effect of good corporate governance on the relationship between intellectual capital disclosure and supply chain. It examines firms listed on the Indonesian stock exchange for period 2013 to 2015. Data were analyzed using moderated regression analysis. Results show that intellectual capital affects the increase of cost of capital. Good corporate governance variable has significant positive effect on cost of capital. Corporate governance could serve as a determinant that influences capital expenditures by investors. The cost of capital is negatively affected by the interaction between intellectual capital disclosure index and good corporate governance. This means that the negative impact of intellectual capital disclosure index on cost of capital is negatively moderated by good corporate governance. Finally it can be concluded that supply chains face increased pressure from stakeholders to incorporate a plethora of corporate responsibility and sustainability aspects in their constituents’ business practices.